SAHKE seismic‐scatter imaging of subduction beneath Wellington, North Island, New Zealand. Issue 9 (7th May 2015) - Kurashimo, Eiji; Henrys, Stuart; Sato, Hiroshi; Iwasaki, Takaya; Okaya, David; Sutherland, Rupert; Stern, Tim; Iidaka, Takashi; Ishiyama, Tatsuya; Savage, Martha
Abstract Scattering reflectivity analysis of onshore seismic data (Seismic Array HiKurangi Experiment) images slab geometry and crustal structure at a geodetically locked subduction boundary. A broad seismic scattering zone (BSZ) up to 10 km thick above the subduction interface at depths of 16–30 km has seismic properties (Vp, Vp/Vs, and Q) that imply high fluid pressures, probably associated with underplated sediments. The listric strike‐slip Wairarapa Fault and other splay faults that sole into the BSZ imply long‐term weakness. High rates of intraslab seismicity with low rates above the slab imply stress decoupling across the BSZ. Association of high fluid pressures and long‐term weakness with geodetic locking is in contrast to similar observations at zones of slow slip at the northern Hikurangi margin and suggest that either (1) pore fluid pressure or locking behavior may cycle over times longer than two decades or (2) local material properties play a significant role in determining if slow slip or locking occurs.